2006
DOI: 10.1103/physrevlett.96.113003
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Spectra of Quantum Aggregates Interacting via Long-Range Forces

Abstract: We present a simple formula by which the shape of the absorption spectrum of an aggregate of quantum "monomers" (cold atoms, molecules, quantum dots, nanoparticles, etc.) interacting via dipole-dipole forces can be calculated from the averaged spectrum of the quantum monomer itself. Spectral broadening, due to a wide variety of causes, is included explicitly so that the formula is applicable not only to the idealization of a discrete spectrum but also to the practical situation of a continuously broadened spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 18 publications
3
44
0
Order By: Relevance
“…Alternatively one can seek approximations. In previous work we have shown that the 'coherent exciton scattering' (CES) approximation gives a good reproduction of experimental aggregate spectra [27,28,32,35] and agrees with exact diagonalisation results for a variety of examples [30,31]. In this approximation, the operator g in the second term on the right hand side of Eq.…”
Section: B Inclusion Of Vibronic Couplingsupporting
confidence: 75%
See 1 more Smart Citation
“…Alternatively one can seek approximations. In previous work we have shown that the 'coherent exciton scattering' (CES) approximation gives a good reproduction of experimental aggregate spectra [27,28,32,35] and agrees with exact diagonalisation results for a variety of examples [30,31]. In this approximation, the operator g in the second term on the right hand side of Eq.…”
Section: B Inclusion Of Vibronic Couplingsupporting
confidence: 75%
“…We use the "coherent exciton scattering" (CES) approximation generalised to be applicable to aggregates of arbitrary size and geometry. This approach can also take the influence of disorder and and temperature implicitly into account [30]. In a previous publication [31] we have tested the CES approximation by diagonalising Hamiltonians of the type considered here.…”
Section: Introductionmentioning
confidence: 99%
“…Approaches to simulate absorption spectra of dimers and aggregates of chromophores have been widely investigated in the literature [1][2][3][4][5][6][7][8][9][10][11][12] and have often been performed in direct connection with experimental results. Moreover, the development of theoretical methods for predicting the spectroscopic properties of dimers, aggregates, and assembly of molecules from first principles calculations remains a contemporary topic, in particular, because such prediction involves several theoretical challenges.…”
Section: Introductionmentioning
confidence: 99%
“…A 3.9 nm increase in FWHM can be attributed to the aggregation of QDs. 45 Further, we have demonstrated the capability of BP in fabricating functional luminescent devices in the area of anticounterfeiting technology. 22 Specifically, high-resolution microscale QR codes are desirable for preventing the forging of IC chips.…”
Section: Resultsmentioning
confidence: 91%